Odpowiedzi

2010-01-15T14:37:42+01:00
4/5-(1,2*5/12-0,8):(-1/8) = 0,8-(6/5*5/12-0,8):(-1/8) =
= 0,8-(0,5-0,8):(-1/8) = 0,8-(-0,3):(-1/8) = 1,1:-1/8 =
= 11/10:-1/8 = -(11/10*8) = -8,8
2010-01-15T15:09:55+01:00
4:5-(1.2*5/12-0,8):(-1/8)
=4:5-(6:12-0,8):(-1:8)
=4:5-(0,5-0,8):(-0.125)
=0,8-(-0,3):(-0.125)
=0,8+0,3:(-0,125)
=0,8+2,4
=3,2

PS: Jakby co to przepisujesz na własną odpowiedzialność. Powodzenia x)
2010-01-15T16:38:00+01:00
4/5-(1,2*5/12-0,8):(-1/8) = 0,8-(6/5*5/12-0,8):(-1/8) =
= 0,8-(0,5-0,8):(-1/8) = 0,8-(-0,3):(-1/8) = 1,1:-1/8 =
= 11/10:-1/8 = -(11/10*8) = -8,8